The development of Virtual Reality (VR) Micro Teaching Laboratory to improve TPACK skills of FISIP-UNY education students - Isfian, Arief Oky; Deni Hardianto; Laila Fatmawati (Universitas Negeri Yogyakarta, 2025)
This study aims to develop a Virtual Reality (VR)-based learning media in the form of a Micro Teaching Laboratory to enhance the Technological Pedagogical Content Knowledge (TPACK) of pre-service teacher students at the Faculty of Social and Political Sciences, Yogyakarta State University.The research employed a Research and Development (RnD) approach using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The research trial involved 48 pre-service teacher students from FISIP UNY. Effectiveness testing was carried out through quantitative analysis, including prerequisite testing (data normality using the Shapiro-Wilk test), effectiveness testing using the Wilcoxon Signed Rank Test, and calculation of Normalized Gain (N-Gain). The results show that the developed VR media is highly feasible based on expert validation. A total of 88% of students showed increased learning scores after using the media. The Wilcoxon test result yielded a significance value of 0.000 (p < 0.05), indicating a significant difference between pre-test and post-test scores. The average pre-test score of 70 increased to 93.33 in the post-test, with an N-Gain score of 0.82, indicating a “high” level of improvement. This media can be accessed anytime and anywhere via the link: https://unyku.id/VirtualRealityUNY. In conclusion, the developed Virtual Reality Micro Teaching Laboratory learning media is proven to be feasible, effective, and innovative in supporting the enhancement of students’ TPACK. These findings contribute to the integration of immersive technology in higher education learning, particularly in the context of micro teaching training.